Unveiling the Mystery of Adult-Onset Still’s Disease: A Compelling Case Report - Daniele Sola; Carlo Smirne; Francesco Bruggi; Chiara Bottino Sbaratta; Aubin Cardin Tamen Njata; Guido Valente; Maria Cristina Pavanelli; Rosetta Vitetta; Mattia Bellan; Lorenzo De Paoli; Mario Pirisi (Life, 2024)
Adult-onset Still’s disease (AOSD) is a rare systemic inflammatory disorder. Diagnosis can take a long time, especially in the presence of confounding factors, and it is, to some extent, a process of exclusion. AOSD has life-threating complications ranging from asymptomatic to severe, such as macrophage activation syndrome (MAS), which is also referred to as hemophagocytic lymphohistocytosis (HLH). This condition is correlated with cytokine storm production and monocyte/macrophage overactivation and typically occurs with rash, pyrexia, pancytopenia, hepatosplenomegaly and systemic involvement. Exitus occurs in approximately 10% of cases. For the treatment of MAS-HLH, the Histiocyte Society currently suggests high-dose corticosteroids, with the possible addition of cyclosporine A, anti-interleukin (IL)-1, or IL-6 biological drugs; the inclusion of etoposide is recommended for the most severe conditions. In all cases, a multidisciplinary collaboration involving the resources and expertise of several specialists (e.g., rheumatologist, infectiologist, critical care medicine specialist) is advised. Herein, we provide a detailed description of the clinical case of a previously healthy young woman in which MAS developed as a dramatic onset manifestation of AOSD and whose diagnosis posed a real clinical challenge; the condition was finally resolved by applying the HLH-94 protocol (i.e., etoposide in combination with dexamethasone).